Customer Experience Factor Analysis Towards Customer Satisfaction Online Shopping - Syahnur, Muh Haerdiansyah; Basalamah, Jafar; Gani, Ackhriansyah Ahmad (Universitas Muhammadiyah Magelang, 2020)
Internet based business leads to high intencity of e-commerce usage. One of the strategics that focused on customer service also known by providing WOW Experience can determine satisfaction with service quality. This research was conducted to customers who have made transactions in e-commerce to see how much influence factors of the customer experience towards e-customer satisfaction. The research method was conducted with an explanatory quantitative approach. The results show that the eight dimensions of customer experience that used in this study simultaneously affected 68.7%. The partial test shows that the Personalize dimension is the most dominant. So, the company is expected to be able to give the impression of customers can be recognized by the presence of e-commerce used.